Abnormal baseline brain activity in Alzheimer's disease patients with depression: a resting-state functional magnetic resonance imaging study. - Liu, Xiaozheng; Guo, Zhongwei; Ding, Yanping; Li, Jiapeng; Wang, Gang; Hou, Hongtao; Chen, Xingli; Yu, Enyan (Neuroradiology, 2017)
Purpose: As one of the most common mental disorders and the most important precursor of suicide in Alzheimer's disease (AD), depression is associated with a decline in both well-being and daily functioning. At present, the diagnosis of AD patients with depression (D-AD) is largely dependent on clinical signs and symptoms, and the precise neural correlate underlying D-AD is still not fully understood. Methods: The current study sought to investigate low-frequency oscillations at the voxel level in D-AD patients based on the amplitude of low-frequency fluctuations (ALFF) measured using resting-state functional magnetic resonance imaging. We examined 22 D-AD patients and 21 non-depressed AD (nD-AD) patients. Results: The results revealed that D-AD patients exhibited increased ALFF values in the left caudate and thalamus and decreased ALFF values in the left middle temporal pole compared with nD-AD patients. Conclusion: These findings may provide further insight into the underlying neuropathophysiology of AD with depression.